Analysis of the Effect of Service Quality, Product Quality and Brand Image on Customer Satisfaction and Its Implications on Consumer Loyalty PT. Sharp Electronics Indonesia (case study at Karawang Sharp Direct Service Station) - Lise Tiasanty; Arifin Sitio (Universitas Mercu Buana, 2022)
This study aims to determine whether there is an influence between service quality, product quality and brand image on customer satisfaction and its implications for consumer loyalty at PT. Sharp Electronics Indonesia (study case in Karawang’ s Sharp Direct Service Station). The research method used was a survey method by distributing questionnaires to 182 respondents who had purchased 32 inch Sharp television LCD products residing in the Karawang’ s Sharp Direct Service Station area and recorded in the Sharp Customer Care Center database. The tool used to analyze data is the Statistical Package for Social Studies (SPSS) program ver.22. The result in this study are (1) Service Quality has positive and significant effect on Customer Satisfaction, (2) Product Quality has positive and significant effect on Customer Satisfaction, (3) Brand Image has positive and significant effect on Customer Satisfaction, (4) ) Service Quality has positive and significant effect on Consumer Loyalty, (5) Product Quality has positive and significant effect on Consumer Loyalty, (6) Brand Image has positive and significant effect on Consumer Loyalty, (7) Customer Satisfaction has positive and significant effect on Consumer Loyalty at PT. Sharp Electronics Indonesia especially at Sharp Direct Service Station (SDSS) Karawang. Positive correlation coefficient with a strong level of interpretation.